2020
DOI: 10.1155/2020/7526037
|View full text |Cite
|
Sign up to set email alerts
|

Poor COVID-19 Preventive Practice among Healthcare Workers in Northwest Ethiopia, 2020

Abstract: Background. The novel coronavirus disease (COVID-19) pandemic outbreak affects the global social, economic, and political context and becomes a significant threat to healthcare providers who are among the exposed groups to acquire and transmit the disease while caring and treating patients. It is crucial to comply with prevention recommendations so as to stay safe and protected. Therefore, this study aimed to assess COVID-19 preventive practice and associated factors among healthcare workers in Northwest Ethio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
55
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(74 citation statements)
references
References 11 publications
14
55
5
Order By: Relevance
“…Availability of soap and bleach and the possibility of isolating suspected cases separately were novel or new variables which were showed statistically significant association with OHS, On the other hand being a male healthcare provider, having work experience of and having a poor attitude towards COVID-19 were had statistically significant association on other studies but not on this study. 16 This study revealed that lack of soap and bleach in health professionals' rooms can decrease health professionals' occupational safety and health (AOR=2.50, 95% CI: 1.439, 4.356). This could be described as shortages of soap and bleach in health professionals "rooms that could influence the handwashing practice of health professionals" before and after patient contact.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Availability of soap and bleach and the possibility of isolating suspected cases separately were novel or new variables which were showed statistically significant association with OHS, On the other hand being a male healthcare provider, having work experience of and having a poor attitude towards COVID-19 were had statistically significant association on other studies but not on this study. 16 This study revealed that lack of soap and bleach in health professionals' rooms can decrease health professionals' occupational safety and health (AOR=2.50, 95% CI: 1.439, 4.356). This could be described as shortages of soap and bleach in health professionals "rooms that could influence the handwashing practice of health professionals" before and after patient contact.…”
Section: Discussionmentioning
confidence: 82%
“…Availability of soap and bleach and the possibility of isolating suspected cases separately were novel or new variables which were showed statistically significant association with OHS, On the other hand being a male healthcare provider, having work experience of and having a poor attitude towards COVID-19 were had statistically significant association on other studies but not on this study. 16 …”
Section: Discussionmentioning
confidence: 99%
“… 19 Another Chinese research study showed that 88% of the healthcare staff were aware of COVID-19 (knowledge score: 8.17 ± 1.30), which was again lower than the current study. 40 The possible reason for the increment of knowledge is due to the accessibility of the information with different media sources in Ethiopia; telecommunication has a default mobile phone sound message during calls about COVID-19 transmission and prevention measures. 15 Despite this, individuals with respiratory disorders are more at risk of developing the disease.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was in agreement with previously conducted studies in Vietnam (79.2%). 40 Therefore, HCWs in different hospitals as well as healthcare system should be very conscious of patients with asthma, COPD, and other chronic diseases since those multi-morbidity patients are associated with highest hospital admission and case fatality rate with severe course of COVID‐19. 42 Thus, we need to increase adequate understanding of participants from time to time about this pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID- 19), is an infectious respiratory disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) [1]. SARS-COV-2 enters into the human cells through angiotensinconverting-enzyme 2 (ACE-2) receptor [2].…”
Section: Introductionmentioning
confidence: 99%